WRIB Poster Award winners. (September 2016) - Unknown
The 10th Workshop on Recent Issues in Bioanalysis (WRIB) was held in Orlando, USA, in April 2016. It drew close to 700 professionals representing large pharmas, biotechs, CROs and multiple regulatory agencies from around the world, working on both small- and large-molecule bioanalysis. This year, bioanalysis and bioanalysis zone were proud to support the WRIB Poster Awards and we feature profiles of the authors of the winning posters. Go towww.bioanalysis-zone.com to see the winning posters in full. Winning posters: